SELF-CARE KNOWLEDGE FOR EPILEPSY PATIENTS UNDERGOING OUTPATIENT TREATMENT AT MY DUC PSYCHIATRIC HOSPITAL IN 2025 (Vietnam Journal of Community Medicine, 2026)
Objectives: Description of the current state of self-care knowledge among outpatient epilepsy patients at My Duc Psychiatric Hospital - Hanoi in 2025. Methods: This is a cross-sectional descriptive study using controlled convenience sampling and a pre-designed toolkit. Results: Epilepsy patients were more male than female (57.1% and 42.9%), and had lower educational levels, with 51.7% having only primary school education. The majority of patients knew how to adhere to medication schedules (69.6%) and avoid stopping medication abruptly (67.8%). However, the rate of correct understanding regarding missed doses and drug interactions was low (50% and 39.3%). Notably, 44.6% still believed they needed to restrain the patient during a seizure, and 46.4% thought they should put an object in the patient's mouth, indicating dangerous misconceptions. Furthermore, 46.4% did not carry their medical card when traveling, and 57.1% did not maintain a seizure diary. Conclusion: Epilepsy patients have limited self-care knowledge, with 32.1% achieving a good level, 42.9% at a fair level, and 25% at an average or poor level.
Keywords: self-care, epilepsy, knowledge